2018
DOI: 10.1159/000490352
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Sleep Restriction Impairs the Antitumor Immune Response in Mice

Abstract: Objectives: Sleep regulates immune function reciprocally and can affect the parameters that are directly involved in the immune response. Sleep deprivation is considered to be a stress-causing factor and is associated with impaired immune activity. It causes increased glucocorticoid concentrations by activating the hypothalamic-pituitary-adrenal axis; this can lead to a series of disorders that are associated with the prolonged or increased secretion of these hormones. The aim of this study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 39 publications
0
24
0
1
Order By: Relevance
“…Sleep does not only affect immune functions related to infection, but also those to several other immune-related pathologies. For instance, sleep disturbances can increase allergic reactions and worsen tumor-related immune responses (138, 226, 289, 404), which indicates that patients with these diseases could profit from sleep improvements. In other situations, however, patients may profit from controlled, short-term sleep deprivation, in analogy to employing sleep deprivation as antidepressive treatment in mood disorders (128).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep does not only affect immune functions related to infection, but also those to several other immune-related pathologies. For instance, sleep disturbances can increase allergic reactions and worsen tumor-related immune responses (138, 226, 289, 404), which indicates that patients with these diseases could profit from sleep improvements. In other situations, however, patients may profit from controlled, short-term sleep deprivation, in analogy to employing sleep deprivation as antidepressive treatment in mood disorders (128).…”
Section: Discussionmentioning
confidence: 99%
“…9 The effect of sleep deprivation on tumor development has also been investigated in experimental studies in mice, and it has been shown that chronic sleep restriction impairs antitumor immune responses and increases growth rate in pulmonary metastasis. 10 However, the results remain inconsistent as several epidemiological studies and meta-analyses have found no association between sleep duration and risk of cancer. 3,11,12 Based on available evidence, no clear consensus about the effect of sleep duration on cancer risk can be drawn as observational studies are susceptible to confounding and reverse causality.…”
Section: Introductionmentioning
confidence: 99%
“…In the beginning, attention was focused on the protective, anti-apoptotic effects of GC on non-lymphoid tumors [151,152]. Later on, several studies explained the effects of endogenous and exogenous GCs not only on the basis of their activity on tumor cells, but also of their immunosuppressive effects, both favoring tumor development [117,153,154] and hampering the response to anti-tumoral drugs [155,156,157]. Therefore, although GCs are still prescribed in patients with cancers for several reasons (i.e., to prevent emesis and hypersensitivity or allergic reactions to anti-tumor drugs, decrease fatigue, and stimulate appetite), it is becoming clear that the use of GCs may be dangerous when prescribed to patients with non-lymphoid tumors.…”
Section: Effect Of Gcs On Treg Cell Number: In Vivo Findings In Tumentioning
confidence: 99%
“…An elegant study evaluated the number of pulmonary metastasis following the injection of B16 cells through the lateral tail vein of mice in which sleep deprivation was induced, thus leading to increased concentrations of endogenous GCs [154]. Lung metastases appeared first in sleep-deprived mice than on control mice, and were in a higher number at the different time points.…”
Section: Effect Of Gcs On Treg Cell Number: In Vivo Findings In Tumentioning
confidence: 99%